The Effectiveness of Interactive Learning Media in Improving Early Childhood Numeracy Skills - Eka Daryati, Melia (JURNAL PENA PAUD, 2025)
The development of interactive media as a type of multimedia teaching aid has a positive impact on children's gross motor skills. This study aimed to determine the effectiveness of interactive media in early childhood education through an experimental study. The study had two participants, 30 children each: An experimental group with interactive teaching media and a control group with conventional teaching methods. Counting skills were assessed before and after the intervention for both groups. Data analysis conducted with a paired t-test showed that the experimental group showed an increase in the mean score from 50 to 80 (t (29) =12.00; p<0.001), indicating a statistically significant difference after the intervention. The Wilcoxon test on the control group showed an increase in the median score from 52 to 60, but did not reach statistical significance (Z=-1.50; p=0.134). The results suggest that the application of interactive teaching media is efficient in improving the counting skills of preschool children compared to traditional methods without focused treatment.